CHAINS OF EDGE-SHARING OPB4 TETRAHEDRA IN THE STRUCTURE OF PB4O(VO4)2 AND IN RELATED MINERALS AND INORGANIC COMPOUNDS - Krivovichev S.V.; Burns P.C. (My University, 2003)
The crystal structure of Pb4O(VO4)(2) has been solved using crystals prepared by high-temperature solid-state reactions. The compound is orthorhombic, Pnma, a 22.7276(9), b 11.5346(4), c 7.4349(3) Angstrom, V 1949.09(13) Angstrom(3), Z = 8. The structure was solved by direct methods and refined on the basis of F-2 of all unique reflections to RI = 0.029 (wR2 = 0.052), calculated for 3052 unique observed reflections. There are six symmetrically independent Pb2+ cations in the structure of Pb4O(VO4)(2). The Pb-O bonds in the PbOn polyhedra range from 2.23 to 3.42 Angstrom and can be subdivided into three groups: short bonds (2.15-2.50 Angstrom), intermediate bonds (2.50-2.70 Angstrom) and long bonds (>2.70 Angstrom). The Pb2+ cations each form from three to five shortand intermediate Pb-O bonds located on one side of the cation. and from three to seven long Pb-O bonds on the other side of the cation. The asymmetry of the distribution of bonds around the Pb2+ cations is due to the stereochemical activity of 6s(2) lone-electron pairs. The structure contains chains of composition [O4Pb8](8+) that involve edge-sharing O(1)Pb-4 tetrahedra. The chains extend along [010] and are arranged into layers parallel to (100). The layers of OPb4 tetrahedra alternate with layers that contain VO4 tetrahedra as well as Pb(1), Pb(3), and Pb(4) atoms. The structural formula of the compound is Pb-2[Pb2O](VO4)(2), which emphasizes the Pb atoms that are not bonded to the additional O-add atoms.
Keywords: lead oxide vanadate; crystal structure; oxocentered tetrahedra